2017
DOI: 10.1111/1748-8583.12168
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating levels of personal role engagement within the working day: A multilevel study

Abstract: In this diary study, we examined a theoretical model in which the psychological conditions of meaningfulness, availability, and safety serve as mechanisms through which the work context during discrete situations within the workday influences "state" engagement. We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 46 publications
(169 reference statements)
1
47
0
3
Order By: Relevance
“…Several quantitative studies have subsequently tested out this model using surveys and diary studies (e.g., Z. Chen, Zhang, & Vogel, 2011; Fletcher, Bailey, & Gilman, 2018; Ganjali & Rezaee, 2016; Geldenhuys, Taba, & Venter, 2014; Gloria & Steinhardt, 2016; Soane, et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several quantitative studies have subsequently tested out this model using surveys and diary studies (e.g., Z. Chen, Zhang, & Vogel, 2011; Fletcher, Bailey, & Gilman, 2018; Ganjali & Rezaee, 2016; Geldenhuys, Taba, & Venter, 2014; Gloria & Steinhardt, 2016; Soane, et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Most often, researchers considered a range of work-related attitudinal outcomes, especially pertaining to work or personal engagement (Fletcher et al, 2018; Geldenhuys et al, 2014; Gloria & Steinhardt, 2016; Johnson & Jiang, 2017), job satisfaction (Duffy et al, 2013), organizational commitment (Leiter & Harvie, 1997), behavioral involvement (Montani et al, 2017), or intrinsic motivation (Johns et al, 1992). All studies found that meaningful work was positively associated with these outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Por fim, as hipóteses H5 e H6 confirmaram o direcionamento das associações, sendo que os recursos do trabalho se associaram de forma positiva com o sentido do trabalho, enquanto as dimensões demanda e assédio moral associaram-se negativamente com o sentido do trabalho. Os achados corroboram estudos anteriores que demonstraram como as percepções de sentido do trabalho podem enriquecer a relação dos trabalhadores com os recursos do trabalho e, consequentemente, favorecer o envolvimento com o trabalho, como também diminuir os impactos das demandas de trabalho (Ahmed, Abdul Majid, Al--Aali, & Mozammel, 2018;Fletcher, Bailey, & Gilman, 2018).…”
Section: Discussionunclassified
“…The Monte Carlo method is a simulation procedure established for statistical testing when other methods are not possible due to restrictions in the data or when variables are interdependent by design (Dezső, Ross, & Uribe, 2016). It has been applied to small data sets in management research (Preacher & Selig, 2012) and to account for the role of context (Fletcher, Bailey, & Gilman, 2018; Peretz, Fried, & Levi, 2018). Using the firm‐specific probabilities that a woman is responsible for HRM (which equals the proportion of WOB), we randomly drew one board member for representing HRM from each organisation and calculated the sum of women drawn from all organisations.…”
Section: Methodsmentioning
confidence: 99%